Restructuring minimum wages: Complexity, compliance and a case for reform - J. R. Shackleton (Institute of Economic Affairs (IEA), 2018)
The National Minimum/Living Wage system has become too complicated, making unintentional non-compliance a problem, and is in danger of becoming a political football. The Low Pay Commission should reject the Taylor Review proposal for new separate minima for workers on zero-hours contracts. We should revert to having just two rates - one for 18-24 year-olds and one for those aged 25 and over. Those under 18 are now required to be in education and training and should not be treated as if they were full-time workers. The 'National Living Wage' title is misleading, suggests that employers have responsibilities which belong to government, and should be dropped. The Low Pay Commission has performed its duties well and should have its powers to recommend rates fully restored. Politicians should not be involved in a bidding war which could damage employment prospects for some groups of workers. However it may be appropriate for the LPC to recommend different rates to the national governments/administrations and possibly also to the London mayor. Rather than HMRC being paid to engage in 'fishing expeditions' to seek out non-compliance, employees should be incentivised to make their own claims by making fines payable as compensation to underpaid workers rather than going to the government. Clearer and more comprehensive guidance on minimum wage regulations should be made available to employers and employees. The policy of 'naming and shaming' non-compliant employers should be confined to those intentionally or negligently underpaying.
Keywords: J30; J33; J38; D31; D61; D63; J30; J33; J38; D31; D61; D63; 330